Determinants of Financial Factors on Cash Dividend Policy: An Empirical Study on The Manufacturing Sector in Indonesia - Kepramareni, Putu; Mirayani, Luh Putri Mas (Juara: Jurnal Riset Akuntansi, 2025)
This study examines the influence of financial ratios on cash dividends in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Utilizing multiple linear regression analysis, this research assesses cash dividends as the dependent variable against independent variables including cash ratio, accounting income, operational cash flow, and earnings per share (EPS). The findings reveal that cash ratio and EPS have a significant positive effect on cash dividends. In contrast, accounting income shows a significant negative influence, while operational cash flow has no significant impact. The model demonstrates strong predictive power, with the independent variables explaining 92% of the variance in cash dividends. These results highlight the critical role of financial ratio analysis for investors in making investment decisions and provide valuable insights for corporate managers in shaping dividend policies.